2021
DOI: 10.1111/ijd.15665
|View full text |Cite
|
Sign up to set email alerts
|

Association between PDCD1 gene polymorphisms and psoriasis susceptibility in the Chinese population

Abstract: Background As an immune regulator expressed on the surface of activated T cells, programmed cell death 1 (PDCD1) plays an important role in psoriasis. However, whether PDCD1 genetic polymorphism is associated with psoriasis has yet to be explored.Objective To study the association between polymorphisms of the immune-related gene PDCD1 and psoriasis susceptibility in the Chinese population, to illustrate the genetic mechanism of psoriasis and provide new research ideas for the diagnosis and treatment of psorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Similarly, in two other separate case-control studies, no associations were detected between PD-1.6 polymorphism and the risk of developing CRC in subjects from Heilongjiang Province in Northeast China [ 2 ] and Eastern China [ 36 ]. However, associations between PD-1.6 polymorphisms and several infectious and autoimmune diseases have been reported in many studies [ 20 , 27 , 29 , 30 , 32 , 55 , 56 ]. For PD-1.5 and PD-1.9 , controversial results have been reported for their association with cancer diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in two other separate case-control studies, no associations were detected between PD-1.6 polymorphism and the risk of developing CRC in subjects from Heilongjiang Province in Northeast China [ 2 ] and Eastern China [ 36 ]. However, associations between PD-1.6 polymorphisms and several infectious and autoimmune diseases have been reported in many studies [ 20 , 27 , 29 , 30 , 32 , 55 , 56 ]. For PD-1.5 and PD-1.9 , controversial results have been reported for their association with cancer diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Variations such as SNPs could influence the gene at the transcriptional level. Several types of cancers and immune diseases have been linked to genetic polymorphisms in the PD-1 and PD-L1 genes [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MMP-9 rs3918242 polymorphism was evaluated in 14 studies with a total of 4733 subjects (2287 cases and 2446 controls) [ 11 , 13 17 , 19 , 20 , 22 , 23 , 25 , 29 , 30 , 32 ]. Genotypes in each of these studies were in HWE.…”
Section: Resultsmentioning
confidence: 99%
“…The MMP-9 rs3918242 polymorphism is a common cytosine-to-thymidine mutation at position -1562 within the MMP-9 gene promoter [ 11 ]. Previous studies have shown that the T allele of this SNP was associated with increased promoter activity and higher MMP-9 levels [ 14 , 23 ]. Given the prominent role of MMP-9 in COPD pathogenesis, dysregulation of MMP-9 expression induced by this SNP may increase the risk of COPD in genotypes containing the T allele.…”
Section: Discussionmentioning
confidence: 99%
“… 110 The G allele of PD1.6 increased the risk of psoriasis in the Chinese subjects. 111 The frequency of the rs2787094 C allele of ADAM33 gene was significantly linked with psoriasis in a Han population. 112 The HCP5 gene 335 T> G polymorphism was associated with the increased risk of developing psoriasis in the Indian patients.…”
Section: The Other Genesmentioning
confidence: 96%